2020
DOI: 10.12911/22998993/123501
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Geometry in Designing and Operating Water Networks

Abstract: Fractals are self-similar sets that cannot be easily described by classical geometry. Fractal sets have been implemented in almost all areas of human activity since they were introduced to science by Mandelbrot in 1982. For the last 10 years, the interest in fractal geometry has increased by the issues connected with water distribution networks (WDNs). The aim of this paper was to review the application of fractal geometry in designing and operating WDNs. Treating a WDN as a fractal pattern enables its descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Fractal geometry has become a very helpful tool used both for the characterization of complex microstructures of porous media and in theoretical analyses to determine the principles of liquid flow through these media. In recent years, the scope of interest in fractal geometry has expanded to include issues related to the design and operation of water supply networks [58]. These are not the only examples of the use of fractal geom-etry as a research tool.…”
Section: Basic Information About Fractal Structuresmentioning
confidence: 99%
“…Fractal geometry has become a very helpful tool used both for the characterization of complex microstructures of porous media and in theoretical analyses to determine the principles of liquid flow through these media. In recent years, the scope of interest in fractal geometry has expanded to include issues related to the design and operation of water supply networks [58]. These are not the only examples of the use of fractal geom-etry as a research tool.…”
Section: Basic Information About Fractal Structuresmentioning
confidence: 99%
“…Diao et al (2017) developed a fractal-based analysis to identify critical pipes in WDSs. A review of the topic can be found in Iwanek et al (2020), while recently, Caldarola and Maiolo (2020) investigated the opportunities of using fractal theory for the description and interpretation of data and dynamics of real complex systems. Finally, a review of the topic of fractal dimension of complex networks has been done by Wen and Cheong (2021).…”
Section: Fractal Geometry Theory and Its Applicationsmentioning
confidence: 99%
“…Furthermore, fractal behavior is not restricted to rough surfaces. It has been shown that a WDN may show fractal properties in its topological structure that may be applied in the analysis of the resilience, reliability, water quality, and operational conditions, as well as in classification, risk assessment, and sectorization procedures (Diao et al 2017;Di Nardo et al 2017;Kowalski et al 2019;Iwanek et al 2020;Kowalska et al 2020;Giudicianni et al 2021). In this context, WDNs have been examined employing graph theory concepts by modeling their underlying topological structure as directed or undirected graphs whose vertices must be covered with the smallest number of boxes or clusters of a certain size (Diao et al 2017;.…”
Section: Introductionmentioning
confidence: 99%